2001
DOI: 10.1017/s0967026201003031
|View full text |Cite
|
Sign up to set email alerts
|

In-line recording of PAM fluorescence of phytoplankton cultures as a new tool for studying effects of fluctuating nutrient supply on photosynthesis

Abstract: Turbidostat cultures of Dunaliella salina (Chlorophyceae) and Thalassiosira weissflogii (Bacillariophyceae) were grown at fluctuating concentrations of nitrate, phosphate and silicate. In-line measurements of PAM fluorescence were used to monitor the effects of fluctuating nutrient supply on the photochemical efficiency of photosystem II reaction centres of light-adapted cells (∆F\F h m ). Besides the maximal photochemical efficiency of photosystem II reaction centres of dark-adapted cells (F v \F m ), chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
2
14
1
Order By: Relevance
“…The quantum efficiency of PSII charge separation (F v /F m ) is widely used as an indicator of the nutrient stress of phytoplankton cells [36], [37], [38]. A reduction in F v /F m as a function of nutrient limitation is generally expected.…”
Section: Discussionmentioning
confidence: 99%
“…The quantum efficiency of PSII charge separation (F v /F m ) is widely used as an indicator of the nutrient stress of phytoplankton cells [36], [37], [38]. A reduction in F v /F m as a function of nutrient limitation is generally expected.…”
Section: Discussionmentioning
confidence: 99%
“…By measuring variable chl fluorescence, the photosynthetic efficiency of cells can be assessed. Many studies have revealed that the supply of N, P, silicate, and iron have strong influences on phytoplankton fluorescence in the field and in the laboratory (Kolber et al 1988, Geider et al 1993a,b, Lippemeier et al 1999, 2001). Most of these studies showed a strong reduction in the fluorescence‐based photochemical efficiency of nutrient limited cells.…”
mentioning
confidence: 99%
“…Most of these studies showed a strong reduction in the fluorescence‐based photochemical efficiency of nutrient limited cells. In‐line measurements of variable fluorescence comprise the direct detection of fluorescence with a glass fiber cable from the culture (Lippemeier et al 2001). The advantage of measuring in‐line fluorescence, in comparison with the typical fluorescence measurements taken in a cuvette, is that in‐line measurements are not influenced by changes in ambient conditions (irradiance, temperature, gas exchange) induced by sample transfer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It can thus be interpreted as a measure of photosynthetic efficiency, and is widely used as an index for the physiological status of phototrophic organisms [9], [19], [22], [31], [32].…”
Section: Methodsmentioning
confidence: 99%